A qualitative study of geriatric specialist nurses' experiences to navigate delirium in the elderly - Mei Wu; Zhen Chen; Yamin Xu; Liting Zhao; Lirong Zhao; Lu Xia (BMC, 2024)
Abstract Background The experiences and perceptions of geriatric specialist nurses are pivotal to understanding the complexities of managing delirium and to developing effective nursing interventions. This qualitative study aims to explore these experiences and perceptions to inform the enhancement of clinical geriatric nursing and care practices. Methods Utilizing a qualitative exploratory design, this research engaged a convenience sample of geriatric specialist nurses at a tertiary hospital in Shanghai, China through focus groups and semi-structured interviews. Data were rigorously analyzed using Colaizzi's phenomenological method, which facilitated the identification of themes that emerged from the narratives of the geriatric specialist nurses. Results The thematic analysis yielded three major themes that encapsulate the nurses' experiences and perceptions. Theme 1: Understanding of Delirium, highlighted the nurses' awareness of the condition's significance, yet it was often deprioritized due to the pressing demands of managing more acute and immediately life-threatening conditions. Theme 2: Barriers in Application, brought to light the multifaceted challenges faced by nurses, including language barriers, the frequency and consistency of delirium assessments, the social determinants of health, and the nurses' own competencies in assessment. Theme 3: Evolution of Nursing Approaches, detailed the adaptive strategies employed by nurses, such as managing nursing adverse events, improving communication with patients' families, and adopting a proactive stance towards long-term patient outcomes. Conclusions The findings suggest that while geriatric specialist nurses recognize the importance of delirium assessment, there are several barriers to effective application. The study underscores the imperative for the advancement of more refined delirium assessment and care protocols, tailored to address the unique requirements of geriatric nursing care.